Trace Elements Induce Predominance among Methanogenic Activity in Anaerobic Digestion - Wintsche, Babett; Glaser, Karin; Sträuber, Heike; Centler, Florian; Liebetrau, Jan; Harms, Hauke; Kleinsteuber, Sabine (Frontiers in Microbiology, 2016)
Trace elements play an essential role in all organisms due to their functions in enzyme complexes. In anaerobic digesters, control and supplementation of trace elements lead to stable and more efficient methane production processes while trace element deficits cause process imbalances. However, the underlying metabolic mechanisms and the adaptation of the affected microbial communities to such deficits are not yet fully understood. Here, we investigated the microbial community dynamics and resulting process changes induced by trace element deprivation. Two identical lab-scale continuous stirred tank reactors fed with distiller’s grains and supplemented with trace elements (cobalt, molybdenum, nickel, tungsten) and a commercial iron additive were operated in parallel. After 72 weeks of identical operation, the feeding regime of one reactor was changed by omitting trace element supplements and reducing the amount of iron additive. Both reactors were operated for further 21 weeks. Various process parameters (biogas production and composition, total solids and volatile solids, trace element concentration, volatile fatty acids, total ammonium nitrogen, total organic acids/alkalinity ratio, and pH) and the composition and activity of the microbial communities were monitored over the total experimental time. While the methane yield remained stable, the concentrations of hydrogen sulfide, total ammonia nitrogen, and acetate increased in the trace element-depleted reactor compared to the well-supplied control reactor. Methanosarcina and Methanoculleus dominated the methanogenic communities in both reactors. However, the activity ratio of these two genera was shown to depend on trace element supplementation explainable by different trace element requirements of their energy conservation systems. Methanosarcina dominated the well-supplied anaerobic digester, pointing to acetoclastic methanogenesis as the dominant methanogenic pathway. Under trace element deprivation, Methanoculleus and thus hydrogenotrophic methanogenesis was favored although Methanosarcina was not overgrown by Methanoculleus. Multivariate statistics revealed that the decline of nickel, cobalt, molybdenum, tungsten, and manganese most strongly influenced the balance of mcrA transcripts from both genera. Hydrogenotrophic methanogens seem to be favored under nickel- and cobalt-deficient conditions as their metabolism requires less nickel-dependent enzymes and corrinoid cofactors than the acetoclastic and methylotrophic pathways. Thus, trace element supply is critical to sustain the activity of the versatile high-performance methanogen Methanosarcina.